3-Oxo-β-Sultams and 4-Oxo-β-Lactams as Chemical Tools for Activity-based Protein Profiling of Serine Hydrolases - Carvalho, Luis Miguel Afonso (2020)
Relatório de projecto final de Doutoramento em Farmácia (Química Farmacêutica e Terapêutica), apresentado à Faculdade de Farmácia da Universidade de Lisboa, 2019.